The social environment and female mate choice - Samuel J. Lymbery; Ana Drago-Rosa; Nick J. Royle; Ana Duarte; David J. Hosken; C. Ruth Archer (Journal of Ethology, 2026)
Female mate choice is a major mechanism of sexual selection, influencing the evolution of behaviour, morphology and life-history. Despite being so important, much about female mate choice remains unclear. Crucially, we have a limited understanding of how mating decisions are affected by the social environment within which these decisions inevitably occur. Here, we review how the social environment influences female mate choice and discuss the wider evolutionary consequences of these effects. We examine important social environment influences on female choosiness (i.e. how much females invest in assessing potential mates), the direction of female preferences (i.e. which phenotypes females prefer) and preference strength (i.e. how strident females are in their preferences). We also consider potential coevolution between mate choice and the social environment arising because both include genes. Finally, we highlight some outstanding questions that help us more fully understand social environment impacts on female mating decisions and emphasize the need for tests of current theoretical predictions.